Relationship between foreign direct investment (FDI) of the service sector and GDP in Malaysia - Tan, Kai Lun; Humaida Banu Samsudin (Penerbit Universiti Kebangsaan Malaysia, 2022)
Foreign direct investment (FDI) has been an important source of economic growth for Malaysia, bringing in capital investment, technology and management knowledge needed for economic growth. Among the sectors in Malaysia, service sector is the main contributor of FDI from other countries. Thus, this study aims to analyse the trend of contributions of FDI from foreign countries in Malaysia. The study also finds the relationship between FDI in service sector and GDP in Malaysia for the year 2010 to 2020 using time series data. Autoregressive Distributed Lag (ARDL) model and empirical analysis are conducted by using quarterly data on FDI in service sector and GDP in Malaysia. The results provide evidence that there is a positive and significant long-run relationship between FDI in service sector and GDP in Malaysia which LFDI rate increase by 1% will lead to the LKDNK rate to increase by 0.15%. However, the empirical evidence has proven that no short-run relationship between FDI in service sector and GDP in Malaysia. Diagnostic tests showed that the residual is normally distributed, free from autocorrelation and heteroscedasticity. This confirms the validity of the ARDL model which is ARDL(3,4).